Diagnosis of Eye Diseases like Glaucoma, Cataract and Diabetic Retinopathy using Illumination Surgical Keratoscope (ISK) and Hierarchical Fuzzy Expert System (HFES) - Rehani, Virat; Kumar, Yogesh (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Glaucoma, Cataract, and Diabetic Retinopathy are ocular conditions characterized by shared symptoms such as elevated eye pressure, optic nerve damage, and potential vision loss. Untreated, these ailments can lead to blindness, particularly affecting peripheral vision. Timely detection of these eye diseases necessitates regular and often expensive checkups, posing a challenge in terms of cost and time. This study introduces a novel approach, employing a Hierarchical Fuzzy-based decision system, to address Glaucoma, Cataract, and Diabetic Retinopathy at their initial stages. Additionally, a cost-effective Surgical Illuminating Keratoscope is proposed to tackle issues related to irregular corneal curvature, cataract surgeries, and Penetrating Keratoplasty. The Hierarchical Fuzzy rule-based system aids medical practitioners in delivering accurate results by taking into account the patients' symptoms. Comprehensive testing of the Hierarchical Fuzzy system and the practicality of the Keratoscope were conducted in collaboration with ophthalmologists. The results, with accuracy, sensitivity, and specificity rates of 93%, 94%, and 92% correspondingly, demonstrate the precision and utility of these systems. Notably, this technique proves to be efficient and incurs low computational costs.